ANALISIS LAJU ALIRAN MASSA FLUIDA DINGIN TERHADAP EFEKTIVITAS PENUKAR KALOR SHELL AND TUBE DESTILLASI MINYAK ATSIRI CENGKEH (Syzygium aromaticum) - Rengga Said; Nicolas Titahelu; Rikhard S. Ufie (ALE Proceeding, 2021)
Shell and tube type heat exchanger is a component of clove essential oil distillation apparatus using hot steam as hot fluid and water as a cold fluid, each flowing in opposite directions. The distillation system in the field still uses a condenser or straight pipe heat exchanger, where the temperature of the hot fluid that comes out is still considered high enough so that the indication of effectiveness is not optimal. To optimize the effectiveness, a shell and tube heat exchanger is designed with a numerical method based on Fluent CFD using a hexagonal pipe geometry in tube layouts of 30Â°, 60Â°, 45Â°, and 90Â° inline and staggered arrangement and counter flow type. This study varied the cold mass flow rate (á¹c) = 0.052; 0.059; 0.083; 0.1; 0.12 Kg/s, while the mass flow rate of the hot fluid is constant. The simulation results obtained that the maximum effectiveness occurred at a mass flow rate of 0.052 kg/s of 5.45% staggered layout and the minimum occurred at a mass flow rate of 0.12 kg/s of 4.01% on an inline layout. The results of this research are also expected to help the community which can be used for various essential oils.